2019
DOI: 10.3389/fphys.2019.00397
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Is Compromised in −12° Head Down Tilt Position

Abstract: Recent studies are elucidating the interrelation between sleep, cranial perfusion, and cerebrospinal fluid (CSF) circulation. Head down tilt (HDT) as a simulation of microgravity reduces cranial perfusion. Therefore, our aim was to assess whether HDT is affecting sleep (clinicaltrials.gov; identifier NCT 02976168). 11 male subjects were recruited for a cross-over designed study. Each subject participated in two campaigns each comprising 3 days and 2 nights. Intervention started on the second campaign day and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
2
8
0
1
Order By: Relevance
“…We propose a possible explanation for venous return, the outflow maybe simultaneously increased via the external jugular vein. As previously described, the minimum cross-sectional area of the external jugular vein, the minimum and maximum cross-sectional area of the internal jugular vein were significantly increased at −12° HDT during this study 8 . One possible explanation of these findings is a shifting from the superficial carotid system towards the internal jugular veins (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…We propose a possible explanation for venous return, the outflow maybe simultaneously increased via the external jugular vein. As previously described, the minimum cross-sectional area of the external jugular vein, the minimum and maximum cross-sectional area of the internal jugular vein were significantly increased at −12° HDT during this study 8 . One possible explanation of these findings is a shifting from the superficial carotid system towards the internal jugular veins (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…We also did not collect any physiological or neurobehavioral data to identify the relevance of the observed phase shifts. Investigation of the acute effects of horizontal bed rest (HBR) and HDBR on sleep revealed a decrease in slow-wave sleep with HDBR ( Komada et al, 2006 ; Boschert et al, 2019 ). Data from long-duration bed rest studies showed that slow-wave sleep and total sleep time decreased after 21 days in HBR and HDBR ( Gkivogkli et al, 2016 ; Morrison et al, 2017 ), suggesting that bed rest per se rather than tilted posture predominantly accounts for sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep deprivation and circadian disturbances are able to induce Aβ and tau accumulation by impairing glymphatic flow (Wu et al., 2019). HDT of −12° under microgravity‐simulating conditions was able to significantly alter sleep quality and brain perfusion in a recent experimental study of physiology during space flight (Boschert, 2019). In another recent MRI study focusing on sleep and the dimension of the perivascular Virchow‐Robin space (VRS) as parts of the glymphatic system (Wardlaw et al., 2020), it could be shown in rats that sleep and VRS dimensions were negatively correlated.…”
Section: Neurovascular Couplingmentioning
confidence: 92%